NEUROLOGICAL DISORDERS IN GLAUCOMA - Siti Hajar; Dessy Rakhmawati Emril; Firjatullah; Rizkidawati (Neurologi Manado, 2021)
Glaucoma is a disease of the visual system that causes permanent blindness. Glaucoma is characterized by degeneration of the trabecular meshwork (TM) (the filter responsible for drainage of aqueous humor from the anterior chamber of the eye), which increases intraocular pressure (IOP). Visual manifestations are first peripheral and then central. Current treatment is primarily aimed at lowering IOP. Currently, IOP is considered only one of the risk factors, and even with a normal IOP, glaucoma can occur. Glaucoma is a multifactorial optic neuropathy characterized by progressive destruction of retinal ganglion cells and their axons characterized by progressive structural loss of retinal ganglion cells (RGCs) and loss of vision. Muller cells play a key role in the maintenance of retinal ganglion cell bodies in the retina. Ganglion cell death in glaucoma is mainly caused by apoptosis which is influenced by various factors that have been identified such as genetic, neurotrophic, autoimmune, and excitotoxic.